2013
DOI: 10.1590/s1517-83822013005000029
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a virulent Leptospira interrogans strain isolated from an abandoned swimming pool

Abstract: Pathogenic Leptospira spp. are the etiological agents of leptospirosis, an important disease of both humans and animals. In urban settings, L. interrogans serovars are the predominant cause of disease in humans. The purpose of this study was to characterize a novel Leptospira isolate recovered from an abandoned swimming pool. Molecular characterization through sequencing of the rpoB gene revealed 100% identity with L. interrogans and variable-number tandem-repeat (VNTR) analysis resulted in a banding pattern i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Blood samples were collected from the retroorbital venous plexus before each immunization and challenge, and the sera were stored at Ϫ20°C. Forty-two days after the first immunization, the hamsters were challenged intraperitoneally with a dose of 10 leptospires, equivalent to 5 times the 50% lethal dose (LD 50 ) (19,31), of the L. interrogans serogroup Icterohaemorrhagiae strain Spool (32). Hamsters were monitored daily and were euthanized upon the appearance of clinical symptoms of leptospirosis.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were collected from the retroorbital venous plexus before each immunization and challenge, and the sera were stored at Ϫ20°C. Forty-two days after the first immunization, the hamsters were challenged intraperitoneally with a dose of 10 leptospires, equivalent to 5 times the 50% lethal dose (LD 50 ) (19,31), of the L. interrogans serogroup Icterohaemorrhagiae strain Spool (32). Hamsters were monitored daily and were euthanized upon the appearance of clinical symptoms of leptospirosis.…”
Section: Methodsmentioning
confidence: 99%
“…Our group characterised this isolate and found that it was highly virulent in the hamster model, causing lesions that are typically associated with severe leptospirosis, with an LD 50 of ~2 leptospires. This indicated that L. interrogans Piscina may pose a risk to public health in the region ( Forster et al 2013 ). Due to its high virulence, this isolate has also been used as a challenge strain in experiments aimed to evaluate the protection afforded by novel recombinant vaccine candidates against leptospirosis in vaccinology laboratories ( Forster et al 2015 ).…”
mentioning
confidence: 99%
“…A wide variety of susceptible animals can host this serovar (FORSTER et al, 2013;LANGONI et al, 2016;RODRIGUES et al, 2015). Maciel et al (2008) investigated seropositivity to the Copenhageni serovar in 269 residents of peripheral neighborhoods in the city of Salvador in Bahia, Brazil, and found that 30% were seropositive, with titers ranging from 25 to 400.…”
Section: Discussionmentioning
confidence: 99%